PVDF-co-HFP/superhydrophobic acetylene-based nanocarbon hybrid membrane for seawater desalination via DCMD - Aljumaily, Mustafa Mohammed; AlSaadi, Mohammed Abdulhakim; Hashim, Nur Awanis; Alsalhy, Qusay F.; Mjalli, Farouq S.; Atieh, Muataz Ali; Al-Harrasi, Ahmed (Elsevier, 2018)
Surface hydrophobicity is the most desirable characteristic for high DCMD performance. Superhydrophobic carbon nanomaterials/powder activated carbon (CNMs/PAC) has unique properties and believed to be the proper candidate to increase the membrane hydrophobicity with maintaining good mechanical properties and high porosity at the same time. In this work, we introduce a phase inversion process based on central composite design, aimed at minimizing the number of experiments required for membrane fabrication. The hydrophobic membrane fabrication conditions are modeled as independent parameters, with the flux provided as the model response. The analyses performed on the membrane structure and surface, as well as its mechanical properties revealed that the superhydrophobic CNMs/PAC significantly enhances the hydrophobicity of the composite membrane surface. The accuracy measurements obtained by analysis of variance showed that the model developed and all the proposed parameters have significant effects on the flux. However, the CNMs/PAC emerged as the most significant influential factor and interacted with polymer concentration and casting knife thickness to exert effects on the permeate flux. The optimum preparation parameters were 775.21 mg carbon loading, PVDF-HFP concentration of 21.86 g and casting knife thickness of 118.93 μm, as these values yield the highest flux of about 102 kg/m2h.